Smegma: Myths and Facts - Gupta , B D (Journal of Indian Academy of Forensic Medicine, 2021)
In relation to sexual intercourse, in cases of rape various textbooks cite presence or absence of smegma under the foreskin of glans  penis and then accordingly interpret the findings. It seems that contemporary literature (which includes various textbooks available for  Undergraduate and Postgraduate students as well as lawyers and judges) unscientifically sees and interprets the presence or absence of  smegma. This paper tries to put myths and facts in their correct perspective. To achieve this, the paper tries to go through the scientific  literature about identification and diagnosis of smegma and limitations prevailing there off in our country and in scientific circle.  Objective of the study is that prevailing unscientific notion can be corrected and miscarriage of justice due to wrong interpretation of  such finding can be avoided. Authors of various textbooks present and future are advised to look into the matter and do necessary  correction in their textbooks.
Keywords: Smegma; Female smegma; Sexual intercourse; Rape; Evidentiary value